ART TEACHING AND DEVELOPING CREATIVITY IN STUDENTS: APPROACHES AND MODELS (Journal of Educational Sciences, 2018)
The article summarizes findings of the research conducted by the Ministry of Education and Science of the Republic of Kazakhstan, «Developing Creativity & Creative Abilities in Students as a Factor of Increasing the Kazakhstan’s Intellectual Capacity». The aim of the research is to design models for creativity development in students, including on the basis of Art Teaching, the development and testing of Art Technologyin the course of teaching students. In the article the following models are given: (1) creativity development in students, (2) synthesis of Art Technology and Psychodrama in playing complex human situations through Puppet Therapy. The model of creativity development in students includes 7 blocks – public order, target, methodological, informative, diagnostic, instrumental, and effective one. It it focused on the following areas (1) use of innovative teaching methods, (2) use of Art Technology for capacity building in students, (3) technology of Puppet Therapy&Psychodrama synthesis. A model of Art Technology&Psychodrama synthesis is proposed by means of shared goals, objectives, principles, functions, and content. The technology of staging complex life situations through Puppet Therapy is described in a step-by-step manner. The first stage is about warming-up: the removal of blocks, exercises in teaching artistry, group ice breaking. The second stage is the core one. During it, the key issue is put at the center, making a doll from improvised material such as newspapers, magazines, role playing around the issue. The third stage is the final one. There occurs discussion and review of the role play. In conclusion section of the article, the use of this technology is reviewed, including evaluation of the technology by students.Key words: art pedagogy, creativity, pedagogical modeling, art therapy, puppet therapy.